2010
DOI: 10.1039/c0cc01699c
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and selective recognition of sulfate anion in an azamacrocycle in water

Abstract: Structural characterization of a sulfate complex with an azamacrocycle suggests that one sulfate is encapsulated in the macrocyclic cavity with eight hydrogen bonds; a significant selectivity of the host was observed for sulfate over halides, nitrate and perchlorate as evaluated by 1 H NMR studies in water.Sulfate is present in the biological system and plays a crucial role in many biochemical processes, 1 such as in biosynthesis 2 and sulfate binding proteins. 3 Sulfate is also a known inorganic pollutant in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 35 publications
0
27
1
Order By: Relevance
“…Kavallieratos and coworkers used an APCI-MS (atmospheric pressure chemical ionization mass spectrometry) for the detection of halides and nitrate with sulfonamides in dichloromethane. 39 Our group recently used ESI-MS to probe a sulfate complex with a thiophene-based monocycle 40 and an octameric phosphate cluster with a tren-based amine. 41 This is a direct method to examine the stability and stoichiometry of a complex in a gaseous state.…”
Section: Resultsmentioning
confidence: 99%
“…Kavallieratos and coworkers used an APCI-MS (atmospheric pressure chemical ionization mass spectrometry) for the detection of halides and nitrate with sulfonamides in dichloromethane. 39 Our group recently used ESI-MS to probe a sulfate complex with a thiophene-based monocycle 40 and an octameric phosphate cluster with a tren-based amine. 41 This is a direct method to examine the stability and stoichiometry of a complex in a gaseous state.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the monohydrogen phosphate is closer to the cavity than the dihydrogen phosphate. The involvement of CH···O interactions is well documented in the literature [21]. Extensive hydrogen bonds between the macrocycle and water molecules are also present.…”
mentioning
confidence: 96%
“…Other reported receptors that are neutral molecules including amides [13], thioamides [14], ureas [15], thioureas [16], pyrroles [17] and indoles [18] were shown to bind phosphate in organic solvents. Our recent studies on various macrocycle-based receptors indicated that hydrogen bonding and electrostatic interactions are major binding forces in stabilizing complexes; thus providing insight into the binding modes of anions and conformations of host molecules [19-21]. Herein, we report the binding aspects of two thiophene-based macrocycles L1 and L2 via 1 H NMR and 31 P NMR in solutions.…”
mentioning
confidence: 99%
“…9 The first encapsulated sulfate with a polyammonium-based host was reported in 2005, where the sulfate was held within the cavity of a m -xylyl-based cryptand via five NH⋯O bonds. 9a Recently, there have been reported several types of neutral hosts including metal–organic cage hosts, 10 polyamides, 11 ureas, 12 thioureas, 13 and indoles; 14 which provide remarkable selectivity and binding affinity for sulfate in organic solvents. For example, Loeb et al reported an encapsulated sulfate within a metal-organic framework containing urea-functionalized quinoline ligands.…”
mentioning
confidence: 99%